2019
DOI: 10.1080/21645515.2019.1608131
|View full text |Cite
|
Sign up to set email alerts
|

Failure of postexposure prophylaxis in a girl child attacked by rabid dog severing her facial nerve causing possible direct entry of rabies virus into the facial nerve

Abstract: On January 4, 2019 an eight-year-old girl child was bitten by a suspected rabid dog over the left parotid region. After a 17-h delay, the child was brought for rabies postexposure prophylaxis (PEP) at Civil Hospital Theog and was administered complete PEP. On January 29, 2019, the child was again brought to Theog Hospital with complaints of having fever, difficulty in walking, neck drop, and ptosis. On examination, pediatrician found photophobia, phonophobia, and hydrophobia and subsequently the patient died o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This PEP failure in a girl child could have been due to many reasons, such as a) there was a delay of 17 hours in seeking PEP, b) the parents of the 8 years old girl child did not immediately wash the wound, c) there was facial nerve involvement, and d) maybe all the wounds were not infiltrated with sufficient eRIG till depth. 17 Animal experiments have proven that even diluted RIG can save lives in experimentally infected mice. 18 We have also used diluted eRIG in many cases having wounds on the head and neck without failure and have advocated that even a small volume of RIG covering the surface of the wound till depth is effective for rabies PEP.…”
Section: Discussionmentioning
confidence: 99%
“…This PEP failure in a girl child could have been due to many reasons, such as a) there was a delay of 17 hours in seeking PEP, b) the parents of the 8 years old girl child did not immediately wash the wound, c) there was facial nerve involvement, and d) maybe all the wounds were not infiltrated with sufficient eRIG till depth. 17 Animal experiments have proven that even diluted RIG can save lives in experimentally infected mice. 18 We have also used diluted eRIG in many cases having wounds on the head and neck without failure and have advocated that even a small volume of RIG covering the surface of the wound till depth is effective for rabies PEP.…”
Section: Discussionmentioning
confidence: 99%
“…True failures of PEP have occurred, although these are admittedly rare, considering that rabies has the highest case-fatality of any infectious disease [ 11 , 12 , 20 ].…”
Section: Would a Fourth Category Make A Difference?mentioning
confidence: 99%
“…We think neuroanatomy is also relevant in consideration of Category IV exposures. Recently, Bharti et al reported a rabies case in a child whose facial nerve was severed, with the postmortem findings of facial nerve dissection at the parotid gland, with noted pathology of swelling and edema of the nerve stump [ 20 ]. Such an exposure is quite serious.…”
Section: Other Considerations For Category IV Exposurementioning
confidence: 99%
“…Integrated Bite Case Management (IBCM) is a recent approach in rabies control for reducing human deaths through enhancing prudent use of PEP. IBCM is a "One Health" approach that aims to establish the health status of the biting animal to inform PEP use [60,91] and reduce human deaths while minimizing unwarranted PEP use [92][93][94]. IBCM has potential to reduce overuse of PEP in lowrisk settings [78], and improve access to PEP in high-risk settings [34].…”
Section: Outcome 13 Human Rabies Is Preventable By Timely Access To Pepmentioning
confidence: 99%